Методичні засади обліку виробничих витрат на олійно-жирових підприємствах в умовах бюджетування - Михальська, О.Л. (Культура народов Причерноморья, 2013)
У статті представлена схема процесу бюджетування та контролю витрат за «центрами відповідальності», що являють собою послідовну логічно-структурну схему виконання комплексу організаційно-методичних, планово-облікових, контрольних та аналітичних робіт; наведена модель формування виробничих витрат за цехами – «центрами відповідальності» в умовах бюджетування на олійно-жирових підприємствах, що є основою методики побудови обліку виробничих витрат і забезпечує інформацією, як для контролю за їх видами і рівнем для цілей бюджетування, так і для аналізу поведінки витрат, що особливо важливо для обґрунтованих розрахунків виробничої собівартості В статье представлена схема процесса бюджетирования и контроля расходов по «центрам ответственности», которые представляют собой последовательную логически- структурная схема выполнения комплекса организационно-методических, планово-учетных, контрольных и аналитических работ; приведена модель формирования производственных затрат по цехам - «центрам ответственности» в условиях бюджетирования масложировых предприятиях, является основой методики построения учета производственных затрат и обеспечивает информацией, как для контроля за их видами и уровнем для целей бюджетирования, так и для анализа поведения затрат, что особенно важно для обоснованных расчетов производственной себестоимости The article gives a description of the main methodological principles of production costs accounting at oil and fat enterprises. The budget of production department of oil and fat enterprises is a functional operational cost flow chart which is needed to be controlled. In this regard, a management accounting system registering economical activity facts (necessary for ensuring a process of budget preparation, control and analysis of developed budget) is supposed to be introduced. Management accounting is the main part of budgeting process. Budget costs preparation, their account, control and analyses of “ Responsibility Centers” is a system which measures and assesses plans and actions of each of them. “Responsibility Centers” accounting is an integral part of internal economical budgeting at all its levels: budgets preparation; their implementation control ant implementation analysis. The main principle of budgets implementation lies is assigning a particular manager of production department to be responsible for budgets implementation ensuring. The results obtain may show that accounting of technological processes functions of oil and fat enterprises makes it possible for analysis to define its weak points in its technical process; define unnecessary technological functions –operations. In its turn, this will facilitate the work of each “Responsibility Center” in ensuring of fixed budget costs specifying “Cost centers” and “Cost centers origin”. The idea is expected to confirm that accounting functional model of the budgeting object can be developed on the basis of interconnections and correlations of the functions-operations of this object. Functional Model is a matrix of connections in the form of description of structural accounting objects operations-functions which appear to be technological conversions.